A comparison of Bai Bithaman Ajil, Musharakah Mutanaqisah and the conventional home mortgages and the effects to the economy / Sheikh Izhar Sheikh Salleh - Sheikh Salleh, Sheikh Izhar (2011)
The purpose of the study is to distinguish special feature of the Islamic financing in particular the home financing product of Bai’ Bithaman Ajil (BBA) and it performance since its inception. Islamic financing is almost the same as other conventional but The Islamic Law (Sharia) prohibits the acceptance of interest fee for the lending and acceptance money unlike the conventional financing used now. This concept refers to the sale of goods on a deferred payment basis at a price, which includes a profit margin agreed to by both parties. This is similar to Murabahah, except that the debtor makes only a single installment on the maturity date of the loan. By the application of a discount rate, an Islamic bank can collect the market rate of interest. There are various institutions that offer this type of Islamic financing in Malaysia throughout the time since the setting up of Islamic bank in Malaysia that complies according National Shariah Advisory Council or to a Shariah Supervisory Board (SSB) to advise them and to ensure that the operations and activities of the bank comply with Shariah principles. On the other hand, there are also those who believe that no form of banking can ever comply with the Shariah. Beside that we can understand more about the process of house financing using Bai’ Bithaman Ajil, concept and application of the principle used in bai’ Bithaman Ajil. The research will try to differentiate the definition concept, and the calculation of the three method of financing